Pricing Decisions of a Dual-Channel Closed-Loop Supply Chain under Uncertain Demand of Indirect Channel - Jie Gao (Mathematical Problems in Engineering, 2016)
The dual-channel closed-loop supply chain (CLSC) which is composed of one manufacturer and one retailer under uncertain demand of an indirect channel is constructed. In this paper, we establish three pricing models under decentralized decision making, namely, the Nash game between the manufacturer and the retailer, the manufacturer-Stackelberg game, and the retailer-Stackelberg game, to investigate pricing decisions of the CLSC in which the manufacturer uses the direct channel and indirect channel to sell products and entrusts the retailer to collect the used products. We numerically analyze the impact of customer acceptance of the direct channel (θ) on pricing decisions and excepted profits of the CLSC. The results show that when the variable θ changes in a certain range, the wholesale price, retail price, and expected profits of the retailer all decrease when θ increases, while the direct online sales price and manufacturer’s expected profits in the retailer-Stackelberg game all increase when θ increases. However, the optimal recycling transfer price and optimal acquisition price of used product are unaffected by θ.